Spirit structures of Papua New Guinea: art and architecture in the Kaiaimunucene - Hirschbichler, Michael (Routledge research in architecture, 2024)
Mythological landscapes -- Cosmos of signs -- Social assemblages -- Ritual spaces -- Art and architecture in the Kaiaimunucene : a transformative conclusion.